Implementing Project Based Learning in English Language Teaching as SMAN 1 Gedangan: Insights from Students - Viona, Anggi; Soraya, Irma; Mujiono, Muhammad (ICONELT, 2024)
This article explores the use of project-based learning (PjBL) in English language teaching at SMAN 1 Gedangan through students’ insight. Using a qualitative research design, data collected through interviews, observations, and a survey of students. The findings showed that PjBL improved students engagement, language proficiency, and critical thinking skills despite challenges such as limited resources, time, and assessment. The study also found that students were more confident when using English in academic and social contexts. PjBL improved their ability to write and speak in a more structured manner and increased their understanding of vocabulary and grammar. This study recommends profesional development, resourch allocation, curriculum integration, flexible scheduling, and assessment training to optimize PjBL and improve English language acquisition. This study emphasizes that continuous support from schools and educators is essential to ensure PjBL is successful. With the right method, PjBL can be an acquire better language skills and skills that fit the modern world.